Collective Bargaining and Increased Competition for Resources in Local Government - Arthur W. Spengler (QUORUM BOOKS, 1999)
Approving the operating budget, levying the taxes to balance it, and establishing the compensation policies for employees are among the most important policy decisions made by many local governments in the United States. The goal of the research reported in this book is to contribute to a better understanding of the nexus between these policy processes in the last decade of the twentieth century. This book explores the use of collective bargaining by full-time local gov- ernment employees in the context of a local budgeting model. It is designed to ascertain if the wave of taxpayer revolts that occurred during the 1970s and early 1980s influenced these employees to use a collective voice strategy as they sought to achieve their goals.